Metabolic and hematological disruptions induced by Diphenyl Diselenide in male wistar rats - Joseph A. Olagunju; Gabriel O. Ajayi; Babatunde A. Murtala; Adejuwan A. Adeneye (The Proceedings of the Nigerian Academy of Science)
Diphenyldiselenide (DPDS), a potent antioxidant and enzyme inhibitor, exerts cellular toxicity mainly through interaction with thiol group of proteins. This study evaluates its toxicity on glycolysis and gluconeogenesis as well as on some hematological parameters in male Wistar rats. Animals were grouped into five with Groups I and II animals intrapenitoneally dosed with 1ml/kg body weight distilled water and olive oil serving as controls while Groups III, IV and V animals were treated with DPDS in olive oil once daily for 21 days at the dose of 50-, 100- and 200mg/kg body weight respectively. All rats were sacrificed on day 21, and plasma, livers and thigh muscles harvested for biochemical assays. Treatment with 200mg DPDS/kg body weight resulted to 100% mortality while 50- and 100mg/kg body weight caused significant reduction (p<0.05) in red blood cell counts, hemoglobin concentration and packed-cell volume. The activities of thigh muscle key glycolytic enzymes along with plasma lactate and liver key gluconeogenic enzymes along with alanine- and aspartate aminotransferases and glycogen were significantly increased (p<0.05) suggesting increased glycolysis and gluconeogenesis respectively in these organs. The increased glycolysis observed may be a consequence of decreased oxygen transport to the peripheral tissue due to reduced hemoglobin hence, increased reliance on anaerobic sources for energy generation. The resultant increased gluconeogenesis and hepatic glycogen storage could be a detoxification mechanism whereby excess lactate due to increased glycolysis is converted to a non-toxic and neutral glucose to maintain pH balance in order to preserve the animals against DPDS toxicity.